ERα status of invasive ductal breast carcinoma as a result of regulatory interactions between lysine deacetylases KAT6A and KAT6B - Mateusz Olbromski; Monika Mrozowska; Beata Smolarz; Hanna Romanowicz; Agnieszka Rusak; Aleksandra Piotrowska (Scientific Reports)
Abstract Breast cancer (BC) is the leading cause of death among cancer patients worldwide. In 2020, almost 12% of all cancers were diagnosed with BC. Therefore, it is important to search for new potential markers of cancer progression that could be helpful in cancer diagnostics and successful anti-cancer therapies. In this study, we investigated the potential role of the lysine acetyltransferases KAT6A and KAT6B in the outcome of patients with invasive breast carcinoma. The expression profiles of KAT6A/B in 495 cases of IDC and 38 cases of mastopathy (FBD) were examined by immunohistochemistry. KAT6A/B expression was also determined in the breast cancer cell lines MCF-7, BT-474, SK-BR-3, T47D, MDA-MB-231, and MDA-MB-231/BO2, as well as in the human epithelial mammary gland cell line hTERT-HME1 – ME16C, both at the mRNA and protein level. Statistical analysis of the results showed that the nuclear expression of KAT6A/B correlates with the estrogen receptor status: KAT6A NUC vs. ER r = 0.2373 and KAT6B NUC vs. ER r = 0.1496. Statistical analysis clearly showed that KAT6A cytoplasmic and nuclear expression levels were significantly higher in IDC samples than in FBD samples (IRS 5.297 ± 2.884 vs. 2.004 ± 1.072, p < 0.0001; IRS 5.133 ± 4.221 vs. 0.1665 ± 0.4024, p < 0.0001, respectively). Moreover, we noticed strong correlations between ER and PR status and the nuclear expression of KAT6A and KAT6B (nucKAT6A vs. ER, p = 0.0048; nucKAT6A vs. PR p = 0.0416; nucKAT6B vs. ER p = 0.0306; nucKAT6B vs. PR p = 0.0213). Significantly higher KAT6A and KAT6B expression was found in the ER-positive cell lines T-47D and BT-474, whereas significantly lower expression was observed in the triple-negative cell lines MDA-MB-231 and MDA-MB-231/BO2. The outcomes of small interfering RNA (siRNA)-mediated suppression of KAT6A/B genes revealed that within estrogen receptor (ER) positive and negative cell lines, MCF-7 and MDA-MB-231, attenuation of KAT6A led to concurrent attenuation of KAT6A, whereas suppression of KAT6B resulted in simultaneous attenuation of KAT6A. Furthermore, inhibition of KAT6A/B genes resulted in a reduction in estrogen receptor (ER) mRNA and protein expression levels in MCF-7 and MDA-MMB-231 cell lines. Based on our findings, the lysine acetyltransferases KAT6A and KAT6B may be involved in the progression of invasive ductal breast cancer. Further research on other types of cancer may show that KAT6A and KAT6B could serve as diagnostic and prognostic markers for these types of malignancies.